PENERAPAN KURIKULUM BERBASIS KOMPETENSI DI PESANTREN DALAM MENCIPTAKAN SANTRI UNGGUL DAN MANDIRI - Noer Rohmah; Roihanah (Pascasarjana Institut Agama Islam Al-Qolam, 2022)
One of the curriculum development processes in Islamic boarding schools is directed at the formation of students who have superior and independent characters as indicators, among others, are obedient to worship, have noble character, have integrity, are able to work well together, do not depend on others and so on. One way to make it happen is to implement a competency-based curriculum, namely a curriculum that emphasizes the emergence of